Dynamic Actin Gene Family Evolution in Primates. (6th June 2013) - Zhu, Liucun; Zhang, Ying; Hu, Yijun; Wen, Tieqiao; Wang, Qiang
Abstract : Actin is one of the most highly conserved proteins and plays crucial roles in many vital cellular functions. In most eukaryotes, it is encoded by a multigene family. Although the actin gene family has been studied a lot, few investigators focus on the comparison of actin gene family in relative species. Here, the purpose of our study is to systematically investigate characteristics and evolutionary pattern of actin gene family in primates. We identified 233 actin genes in human, chimpanzee, gorilla, orangutan, gibbon, rhesus monkey, and marmoset genomes. Phylogenetic analysis showed that actin genes in the seven species could be divided into two major types of clades: orthologous group versus complex group. Codon usages and gene expression patterns of actin gene copies were highly consistent among the groups because of basic functions needed by the organisms, but much diverged within species due to functional diversification. Besides, many great potential pseudogenes were found with incomplete open reading frames due to frameshifts or early stop codons. These results implied that actin gene family in primates went through "birth and death" model of evolution process. Under this model, actin genes experienced strong negative selection and increased the functional complexity by reproducing themselves.